2020
DOI: 10.1111/jfpp.14751
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different application methods of sumac (Rhus coriaria) and tarragon (Artemisia dracunculus) on some quality properties of marinated sea bream (Sparus aurata L., 1758)

Abstract: Marinades are favorite semi-preserved ready to eat food, which is formed by the action of acetic acid and salt from past to present

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…Some quality parameters (chemical, microbiological, and sensorial) of sumac and tarragon added sea bream marinades which studied in our same project showed in Çorapcı et al. (2020). There have been no studies in the literature evaluating the addition of sumac and tarragon spices to marinades on proximate, TBARs, and fatty acids.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…Some quality parameters (chemical, microbiological, and sensorial) of sumac and tarragon added sea bream marinades which studied in our same project showed in Çorapcı et al. (2020). There have been no studies in the literature evaluating the addition of sumac and tarragon spices to marinades on proximate, TBARs, and fatty acids.…”
Section: Introductionsupporting
confidence: 57%
“…The study (Corapci et al., 2020) conducted within the scope of the same project, it was reported that the total mesophyll aerobic bacteria load of the groups exceeded the limit value (10 6 ), primarily in the brewing groups. In this study, the TBARs content of the brew groups was maximum on day 180.…”
Section: Resultsmentioning
confidence: 98%
“…It has preservative properties, so it is keenly used for pickling cabbage and cucumbers, marinating pumpkins, and for the production of tarragon mustard and herbal vinegars. It is recommended for people on a salt-free diet because it improves the taste of dishes ( Kordali et al, 2005 ; Méndez-Del Villar et al, 2016 ; Çorapcı et al, 2020 ). It is also added to infusions, refreshing drinks, alcoholic and non-alcoholic drinks such as “Tarkhun” – a carbonated, non-alcoholic drink, the main ingredient of which are fresh A. dracunculus leaves.…”
Section: Applications In the Food Industrymentioning
confidence: 99%
“…In Slovenia, tarragon is used to season the pastry called ‘potica’. In the United States, it is added to vinegar, tartar sauce and seafood ( Goldstein, 1999 ; Ribnicky et al, 2004 ; Aglarova et al, 2008 ; Çorapcı et al, 2020 ).…”
Section: Applications In the Food Industrymentioning
confidence: 99%
“…The aim is not only to prevent microorganism growth but also it is used to tenderize or to change the taste, textural structural properties of raw materials (Gökoğlu et al 2004). Studies on the use of marination technology in the processing of seafood are available in the literature (Gökoğlu et al 2004;Kılınç & Çaklı 2004;Kılınç & Çaklı 2005;Kaba et al 2014;Moreno et al2017;Turan et al 2017;Keskin et al 2018;Kocatepe et al 2019;Testa et al 2019;Çorapcı et al 2020;Szymczak et al 2020;Çorapcı et al 2021). The researchers studied the effects of marination under refrigerator conditions at different salt and acid concentrations in different fish species.…”
Section: Introductionmentioning
confidence: 99%